ONLINE ENGLISH LEARNING DURING COVID-19 PANDEMIC FOR STUDENTS OF SMA NEGERI 4 MEDAN - Febrianty Lumbantobing; Roganda Simamora; Melany Lorenza Sirait; Inry Surya Angelina Simanjuntak; Azizah Husda (English Language Teaching Prima Journal (ELT), 2021)
Abstract Online learning is one of the alternatives that can overcome the COVID-19 pandemic that is endemic in 2021. This is very troubling to the community, especially disrupting learning in schools. Students who want to learn are constrained by the outbreak of the disease, so solutions are needed to overcome these problems. The purpose of this study was to get an overview of the implementation of online learning at SMA Negeri 4 Medan as an effort to suppress the spread of COVID-19 in school. The research subjects are students of the Biology Education Study Program. Data collection is done by interviewing through zoom cloud meeting. Data analysis was carried out using the Miles & Huberman interactive analysis technique. Weak supervision of students, limited signal in remote areas and high internet costs are challenges in online learning. However, many benefits can be obtained from online learning, including increasing learning independence, interest and motivation, and the courage to express ideas and questions. The results showed that: (1) students had the basic facilities needed to participate in online learning; (2) online learning has flexibility in its implementation and can encourage the emergence of self-regulated learning and motivation to be more active in learning, and (3) distance learning encourages the emergence of social distancing behavior and minimizes the emergence of student crowds which are considered to reduce the potential for spreading COVID-19 in the campus environment. Keywords: Online English Learning, Overcome Covid-19